Study and Implementation of Resource Allocation Algorithms in Cloud Computing - Salman Chyad, Haitham; Ali Mustafa, Raniah; Thabt Saleh, Kawther (International Journal of Engineering and Technology, 2018)
Now days, cloud based implementations are very prevalent and used widely for different types of services. At the point of deployment of cloud computing, there are enormous data centers and the associated virtual machines which work as per the scheduling and resource allocation approaches so that higher degree of optimization, accuracy and performance can be achieved from the cloud environment. The work presents the use of soft computing for the optimization and scheduling of the resources with the higher performance on cloud. This manuscript is having the key focus on the study and implementation of resource allocation and scheduling approaches in the cloud environment whereby there are enormous algorithms are integrated to escalate the overall performance of the cloud environment.Â